Pengaruh Media Pembelajaran Berbantuan Aplikasi Canva terhadap Hasil Belajar Siswa Kelas IV SD PAB 23 Patumbak - Feby Carera; Nurmairina Nurmairina (Journal on Education, 2024)
This study aims to determine the influence of student learning outcomes in IPAS Learning Force Material through Canva Application Assisted Learning Media which is motivated by the low student learning outcomes caused by the lack of innovation in the learning media used so that it makes students less active in the learning process. This type of research is an experimental study using a quasi-experiment research design with the chosen design is Quasi Experimental Design which is carried out in collaboration between researchers and teachers in improving student learning outcomes by using Canva Application Assisted Learning Media. The population in this study were all grade IV students at SD PAB 23 Patumbak, the samples in this study were Class IV A as the experimental class and class IV B as the control class totaling 30 students each. Data analysis techniques were carried out using the t test for all hypotheses. The instrument in this study was a multiple choice test sheet. Based on the results of the study, it shows that the calculation of the t test, tcount < ttable, namely (0.601 < 2.02) so that Ha is accepted and Ho is rejected. Thus it can be concluded that there is a significant influence and how much influence the learning media assisted by the Canva application has on student learning outcomes in learning science and style material in class IV at SD PAB 23 Patumbak.